2004
DOI: 10.1111/j.1472-765x.2004.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro new dialysis protocol to assay the antiseptic properties of a quaternary ammonium compound polymerized with denture acrylic resin

Abstract: Aims: To develop an in vitro protocol in order to assess the antiseptic properties of a quaternary ammonium compound polymerized with acrylic denture resin base, using experimental resin discs and dialysis membranes. Methods and Results: Experimental acrylic resin discs were polymerized with Poly 202063A, an ammonium compound (2-50%). Antiseptic properties were assayed against two reference strains (Escherichia coli, Staphylococcus aureus) and a laboratory strain (Candida albicans), using three different condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
1
28
0
6
Order By: Relevance
“…The first one pertained to the degree of conversion of acrylic resin. Some studies reported that the Fs value decreased with increase in the content of other compounds added to acrylic resin 30,39) . In the context of the present study, the degree of conversion of acrylic resin might be adversely affected because of the addition of other material namely TiO2 or Ap-TiO2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one pertained to the degree of conversion of acrylic resin. Some studies reported that the Fs value decreased with increase in the content of other compounds added to acrylic resin 30,39) . In the context of the present study, the degree of conversion of acrylic resin might be adversely affected because of the addition of other material namely TiO2 or Ap-TiO2.…”
Section: Discussionmentioning
confidence: 99%
“…Against this backdrop of functional and costrelated reservations toward denture cleansers, several researchers have attempted to mix acrylic resins with antifungal agents, antiseptics, a silver inorganic system, and organic materials for additional antibacterial effects [29][30][31][32] . These previous studies showed that the added antifungal and antiseptic agents were rapidly released from denture bases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Pesci-Bardon et al 61,62) have performed a study that a quaternary ammonium compound was incorporated into an acrylic denture resin base in different concentrations, and the antimicrobial properties to Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Candida albicans (C. albicans) were tested. It was shown that 2% quaternary ammonium compound polymerized with a denture acrylic resin displayed antimicrobial properties after a 4-week soaking period in artificial saliva.…”
Section: Acrylic Resinmentioning
confidence: 99%
“…Além disso, a menor destreza manual de pacientes idosos prejudica a higiene bucal e predispõe a instalação da estomatite protética (BUDTZ-JORGENSEN, 1978). Essa condição geralmente não é considerada séria, entretanto pode resultar num processo inflamatório crônico e agir como um foco de infecção (BUDTZ-JORGENSEN, 1978), especialmente em pacientes que apresentam alguns fatores sistêmicos como diabetes mellitus, AIDS, doenças neoplásicas, quimioterapia, radioterapia e terapia antibiótica de largo espectro (PESCI-BARDON et al, 2004).…”
Section: Introductionunclassified
“…Diversos materiais têm sido testados com intuito de diminuir a aderência de microorganismos à resina acrílica como a adição de clorexidina (LAMB & MARTIN, 1983), compostos quaternários de amônio (PESCI-BARDON et al, 2004), radicais fosfato (PURI et al, 2008), zeólito de prata-zinco (CASEMIRO et al, 2008) e outros.…”
Section: Introductionunclassified